Blockchain Technology in AI-Driven Cybersecurity: Strengthening Trust in Financial and Digital Security Systems - Zangana, Hewa (PT. SNN MEDIA TECH PRESS, 2025)
Blockchain technology has revolutionized the banking and finance sector by introducing a decentralized, secure, and transparent framework for financial transactions. This paper provides a comprehensive review of the role of blockchain in transforming trust mechanisms within financial institutions, focusing on its applications in payments, smart contracts, identity management, and regulatory compliance. A mixed-methods approach was employed, integrating a systematic literature review with case study analysis to evaluate the effectiveness of blockchain-based security solutions. The results indicate that blockchain significantly enhances transaction security, reduces fraud, and improves operational efficiency, with AI-powered fraud detection achieving a 92% accuracy rate and biometric authentication strengthening access control. Despite these advantages, challenges such as scalability, regulatory compliance, and integration with existing financial infrastructures remain key barriers to adoption. The study concludes that blockchain, in conjunction with AI-driven cybersecurity measures, presents a robust solution for enhancing trust and security in digital finance. However, continuous regulatory advancements and industry-wide collaboration are necessary to ensure its sustainable implementation.